2016
DOI: 10.3390/su8060581
|View full text |Cite
|
Sign up to set email alerts
|

Soil Seed Bank and Plant Community Development in Passive Restoration of Degraded Sandy Grasslands

Abstract: Abstract:To evaluate the efficacy of passive restoration on soil seed bank and vegetation recovery, we measured the species composition and density of the soil seed bank, as well as the species composition, density, coverage, and height of the extant vegetation in sites passively restored for 0, 4, 7, and 12 years (S0, S4, S7, and S12) in a degraded grassland in desert land. Compared with S0, three more species in the soil seed bank at depths of 0-30 cm and one more plant species in the community was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
3
18
1
Order By: Relevance
“…There is contradictory evidence in the literature concerning the contribution of seed banks to the restoration of dry grasslands. Some authors argue that the soil seed bank can play an important role in the restoration of degraded sites, such as in Estonian calcareous grasslands (Kalamees et al ) or in Chinese sandy grasslands (Miao et al ). Our results showed that dry grassland specialist species already missing from the vegetation communities are no longer present in the soil seed bank.…”
Section: Discussionmentioning
confidence: 99%
“…There is contradictory evidence in the literature concerning the contribution of seed banks to the restoration of dry grasslands. Some authors argue that the soil seed bank can play an important role in the restoration of degraded sites, such as in Estonian calcareous grasslands (Kalamees et al ) or in Chinese sandy grasslands (Miao et al ). Our results showed that dry grassland specialist species already missing from the vegetation communities are no longer present in the soil seed bank.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) The effects of abandonment depend on the grassland type and we expect that, due to their low density and low diversity seed bank, restored loess grasslands are more sensitive to abandonment than restored alkaline grasslands (Tóth & Hüse 2014; Valkó et al 2014). (iii) The effect of abandonment is more pronounced in the vegetation of the restored grasslands than in the seed bank as vegetation dynamics are generally faster than seed bank dynamics (Miao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ex-closures are rehabilitation techniques where, degraded land areas are closed off from the interference of human and domestic animals to lessen land degradation of formerly degraded open grazing lands, promoting natural regeneration of plants and replenish biodiversity and restore soil fertility [5][6][7] . In ex-closures practices, it is believed that a degraded ecosystem recovers readily by itself in the absence of stress or disturbance through what is termed as "passive restoration" 8 .…”
Section: Study Of Soil Seed Banks In Ex-closures For Restoration Of Dmentioning
confidence: 99%